THE ABKHAZIAN HOLIDAY OF AJYRNYH”WA OR THE DAY OF THE CREATION OF THE WORLD. TRADITION AND MODERNITY - Ajba, Tamara Guramovna (History, Archeology and Ethnography of the Caucasus, 2023)
In the article, the author analyzes the transformation of the Azhyrnyҳәa holiday - the day of the creation of the world - which is celebrated in Abkhazia in honor of the onset of the "Abkhaz New Year" on the night of January 13-14. Azhyrnyҳәa is one of the oldest and main traditional Abkhazian holidays, which has survived to the present day. The Abkhazians preserved this cult, since the production of metal objects itself was developed at a high level. The prominent role of metal tools and weapons in people’s lives could not but be reflected in their worldview and religious beliefs. The great power of metal, which gave a huge shift to the development of mankind, was noted and elevated to a cult, expressed in worship and sacrifice. Due to the fact that the smelting of metal and the original method of processing it were very complex, almost inaccessible, it seemed to people that this work was associated with some kind of supernatural, inexplicable forces. ku This holiday is accompanied by annual prayers with sacrifices. So, in all likelihood, the process of formation of the cult of the blacksmith, the blacksmith’s craft and the patron of this craft, Shyashy, took place. The author analyzes ethnographic studies and collected data, exploring the changes that have taken place in the prayer ritual in the post-Soviet period. The article also provides field materials on the reconstruction by Turkish Abkhazians of the traditional Abkhazian holiday Azhyrnyҳәa within the framework of the diaspora, which has become one of the means of expressing the original Abkhazian traditional culture abroad.